The Gospel of John and the future of Israel - Blumhofer, Christopher 1983- (Society for New Testament studies monograph series, 2020)
The Gospel of John is renowned for the challenges it presents to interpreters: its historical complexity, theological and literary unity, and its consistently critical stance toward characters known as 'the Jews'. There is abundant scholarly literature on each of these challenges, and yet there are very few studies that consider the Gospel as a whole in light of these pressing issues. Mark Blumhofer offers a fresh approach to understanding the Fourth Gospel, one that draws together the insights of scholarship in all of these areas. He shows that a historically sensitive, ethically attuned, and theologically and literarily compelling reading of the Fourth Gospel lies before us in the synthesis of the approaches that have long been separated. Unlike studies that consider only a narrow portion of the Gospel, Blumhofer's unique approach draws on most of it and shows how common themes and interests run throughout the narrative of John